2022
DOI: 10.1093/eurheartj/ehac689
|View full text |Cite
|
Sign up to set email alerts
|

Combining loop with thiazide diuretics for decompensated heart failure: the CLOROTIC trial

Abstract: Aims To evaluate whether the addition of hydrochlorothiazide (HCTZ) to intravenous furosemide is a safe and effective strategy for improving diuretic response in acute heart failure (AHF). Methods and results A prospective, double-blind, placebo-controlled trial, including patients with AHF randomized to receive HCTZ or placebo in addition to an intravenous furosemide regimen. The coprimary endpoints were changes in body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 25 publications
(33 reference statements)
4
139
1
3
Order By: Relevance
“…Yet, assuming that the effect of SGLT2 inhibitor on volume homeostasis occur and are durable, it is difficult to know if treatmentmediated changes in the volume set point (if any) contribute to the effect of these drugs to reduce the risk of major heart failure events. Short-or long-term use of many conventional natriuretic and aquaretic drugs has not reduced cardiovascular death or hospitalizations for heart failure, 136,[138][139][140]157 demonstrating that immediate changes in urinary sodium or water excretion do not yield long-term clinical benefits. It is possible that the effects of SGLT2 inhibitors on sodium avidity may differ from other agents, but the volume effect of these drugs is small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, assuming that the effect of SGLT2 inhibitor on volume homeostasis occur and are durable, it is difficult to know if treatmentmediated changes in the volume set point (if any) contribute to the effect of these drugs to reduce the risk of major heart failure events. Short-or long-term use of many conventional natriuretic and aquaretic drugs has not reduced cardiovascular death or hospitalizations for heart failure, 136,[138][139][140]157 demonstrating that immediate changes in urinary sodium or water excretion do not yield long-term clinical benefits. It is possible that the effects of SGLT2 inhibitors on sodium avidity may differ from other agents, but the volume effect of these drugs is small.…”
Section: Discussionmentioning
confidence: 99%
“…Although intensive short-term diuresis to achieve hemoconcentration in hospitalized patients is associated with lower cardiac filling pressures, 153 early decongestion has not been associated with improved outcomes in observational studies or clinical trials. 138–141,154,155 More intensive treatment with intravenous loop diuretics yields a greater short-term diuresis, but does not reduce heart failure events at 60 days. 138 The addition of hydrochlorothiazide to a loop diuretic yields a modest diuretic effect, but no effect on death or rehospitalization at 90 days.…”
Section: Effect Of Sglt2 Inhibitors On Edema and Congestionmentioning
confidence: 99%
“…The Safety and Efficacy of the Combination of Loop with Thiazide-type Diuretics in Patients with Decompensated Heart Failure (CLOROTIC trial; NCT01647932) 7 evaluated if addition of hydrochlorothiazide (HCT) to intravenous furosemide is a safe and effective strategy for improving diuretic response in patients with AHF. In total, 230 patients (48 women, 83 years) were randomized to HCT or placebo; those on HCT lost more weight at 72 h [2.3 vs. 1.5 kg; 1.14 (95 CI 1.84 to 0.42); P 0.002], but there were no significant differences in patient-reported dyspnoea.…”
mentioning
confidence: 99%
“…The efficacy of using hydrochlorothiazide with a loop diuretic was examined in the Safety and Efficacy of the Combination of Loop with Thiazide-type Diuretics in Patients with Decompensated Heart Failure (CLOROTIC) trial, which randomized 230 patients admitted for acute decompensated heart failure to either thiazide plus loop or loop diuretic alone. 53 It showed greater weight loss in the combined arm, but with higher rates of a rise in serum creatinine >0.3 mg/dl. A number of observational studies have shown thiazide diuretics to be efficacious in acute decompensated heart failure, even at low GFR.…”
Section: Therapies For the Cardiorenal Syndromementioning
confidence: 89%